Application of Augmented Reality Technology to Present Local Wisdom: Case Study of Muang Kaen Phatthana Town Municipality, Mea Tang District, Chiang Mai Province - Rattachuchok, Ponwana (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2022)
The objectives of this research were to develop the application of augmented reality to present local wisdom on android operating system and to study users’ satisfaction for application of augmented reality to present local wisdom. The studied sample groups consist of 15 informants of local wisdoms by using the purposive sampling method, 5 experts as quality assessment samples using the purposive sampling method and 30 users samples by using the simple random sampling method. The research instruments consisted of interview, questioning, evaluation form, and satisfaction assessment form. Data were analyzed by descriptive statistics, mean, and standard deviation. The results revealed that data on 15 local wisdom could be collected and such obtained data were applied to make a book for transferring knowledge that was presented in the Augmented Reality application. The Augmented Reality application was assessed on its efficiency by the experts with mean of 4.12 and high level of appropriateness before using. The results of the satisfaction assessment conducted by users revealed that satisfaction was at a high level with mean of 4.26 and standard deviation of 0.52. Application can be used to conservation and learn of local wisdom.